Are we still modern? Inheritance law and the broken promise of the enlightenment - Jens Beckert (Max Planck Institute for the Study of Societies, 2010)
The regulation of the transfer of property mortis causa has been a major concern of social reformers since the Enlightenment. Today, by contrast, the issue of the bequest of wealth from generation to generation stirs hardly any political controversy. Since the mid-twentieth century the topic has lost much of its earlier significance in public debates. In this working paper I show that over the last forty years we can observe a backlash in key areas of inheritance law which breaks the Enlightenment's promise to distribute wealth in society based on individual achievement rather than ascriptive criteria. Hence the question: 'Are we still modern?' – – Die Regulierung der Vermögensvererbung war wichtiger Gegenstand von Sozialreformen seit der Aufklärung. Heute hingegen erregt der Umgang mit Erbschaften kaum noch politische Aufmerksamkeit. Seit der zweiten Hälfte des zwanzigsten Jahrhunderts hat das Thema seine Bedeutung im öffentlichen Diskurs verloren. Das Working Paper zeigt einen Backlash in zentralen Bereichen des Erbrechts während der letzten vierzig Jahre auf, durch den mit dem Versprechen der Aufklärung gebrochen wird, Reichtum nicht nach Kriterien der Herkunft, sondern nach Maßstäben von Leistung zu verteilen. Daher die Frage: 'Sind wir noch modern?'
Keywords: 300; Erbrecht; Sozialreform; Deutschland